Graphene quantum dots conjugated albumin nanoparticles for targeted drug delivery and imaging of pancreatic cancer - Nigam, Preeti; Waghmode, Shobha; Louis, Michelle; Wangnoo, Shishanka; Chavan, Pooja; Sarkar, Dhiman (Journal of Materials Chemistry B, 2014)
Pancreatic cancer is considered to be the deadliest of all cancers due to its poor prognosis and resistance to conventional therapies. In this study, the potential of hyaluronic acid functionalized and green fluorescent graphene quantum dot (GQD)-labeled human serum albumin nanoparticles for pancreatic cancer specific drug delivery and bioimaging was explored. GQDs with tunable fluorescence properties and biocompatibility have attracted much more interest in recent years as compared to their metal semiconductor counterparts. We adopted lawsone (2-hydroxy-1,4-naphthoquinone) as a novel reducing agent for the synthesis of quantum dots and, in addition to excellent fluorescence of the synthesized GQDs, a good quantum yield of similar to 14% was also obtained. Gemcitabine, the most preferred drug for pancreatic cancer treatment, was encapsulated in albumin nanoparticles, and it was observed that our nanoformulation significantly enhanced the bioavailability and sustained release property of the drug to pancreatic cancer cells in vitro. Moreover, the GQD-mediated bioimaging was excellent and enhanced the efficacy of our system as a drug delivery vehicle.

Green synthesis of silver nanoparticles from purple acid phosphatase apoenzyme isolated from a new source limonia acidissima - Pawar, Omkar; Deshpande, Neelima; Dagade, Sharda; Waghmode, Shobha; Joshi, Preeti Nigam (Journal of Experimental Nanoscience, 2016)
Green synthesis of nanoparticles is regarded as a safe and non-toxic process whereas conventional synthesis using chemical methods produces toxic substance. This study provides a novel insight for enzymatic synthesis method of silver nanoparticles using purple acid phosphatase, isolated from Limonia acidissima (wood apple) as a new source and used in the synthesis of silver nanoparticles. Stable silver nanoparticles were produced by sonochemical method using apoenzyme as a stabilising and capping agent and were characterised by various physicochemical techniques like UV-Visible spectroscopy, Fourier-transform infrared, X-ray diffraction and transmission electron microscopy. X-ray study shows that nanoparticles are composed of silver and silver oxide. The synthesised nanoparticles exhibited excellent antimicrobial activity against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus.
Keywords: green synthesis; Limonia acidissima; purple acid phosphatase; silver nanoparticles